Understanding the Impact of Pulmonary Rehabilitation on Airway Resistance in Patients with Severe COPD: A Single-Center Retrospective Study - Kiliç L; Tural Önür S; Gorek Dilektasli A; Ulubay G; Balcı A (International Journal of COPD, 2023)
Lütfiye Kiliç,1 Seda Tural Önür,2 Aslı Gorek Dilektasli,3 Gaye Ulubay,4 Arif Balcı5 1Yedikule Chest Diseases and Thoracic Surgery Training and Research Hospital, Pulmonologist, Department of Pulmonary Rehabilitation, University of Health Sciences, Istanbul, Turkey; 2Yedikule Chest Diseases and Thoracic Surgery Training and Research Hospital, Associate Professor, Department of Chest Diseases, University of Health Sciences, Istanbul, Turkey; 3Uludağ University, Faculty of Medicine, Associate professor, Department of Chest Diseases, Bursa, Turkey; 4Başkent University, Faculty of Medicine, Professor, Department of Chest Diseases, Ankara, Turkey; 5Yedikule Chest Diseases and Thoracic Surgery Training and Research Hospital, Physiotherapist, Department of Pulmonary Rehabilitation, University of Health Sciences, Istanbul, TurkeyCorrespondence: Lütfiye Kiliç, Yedikule Chest Diseases and Thoracic Surgery Training and Research Hospital, Istanbul, Turkey, Tel +90 532 397 7172, Email lutuf1@yahoo.comPurpose: We investigated the effect of pulmonary rehabilitation (PR) on airway resistance in chronic obstructive pulmonary disease (COPD) patients with severe airway obstruction and hyperinflation.Patients and Methods: This retrospective cohort study was conducted with data from severe COPD cases with those who underwent an 8-week PR program. Main inclusion criteria were having severe airflow obstruction (defined as a forced expiratory volume in one second (FEV1) < 50%) and plethysmographic evaluation findings being compatible with hyperinflation supporting the diagnosis of emphysema (presence of hyperinflation defined as functional residual capacity ratio of residual volume to total lung capacity (RV/TLC) > 120%). Primary outcomes were airway resistance (Raw) and airway conductance (Gaw) which were measured by body plethysmography, and other measurements were performed, including 6-minute walk test (6-MWT), modified Medical Research Council dyspnea scale (mMRC) and COPD assessment test (CAT).Results: Twenty-six severe and very severe COPD patients (FEV1, 35.0 ± 13.1%; RV/TLC, 163.5 ± 29.4) were included in the analyses, mean age 62.6 ± 5.8 years and 88.5% males. Following rehabilitation, significant improvements in total specific airway resistance percentage (sRawtot%, p = 0.040) and total specific airway conductance percentage (sGawtot%; p = 0.010) were observed. The post-rehabilitation mMRC scores and CAT values were significantly decreased compared to baseline results (p < 0.001 and p < 0.001, respectively). Although there were significant improvements in 6-MWT value (p < 0.001), exercise desaturation (ΔSaO2, p = 0.026), the changes in measured lung capacity and volume values were not significant.Conclusion: We concluded that PR may have a positive effect on airway resistance and airway conductance in COPD patients with severe airflow obstruction.Keywords: airway resistance, body plethysmography, airflow limitation, emphysema, lung mechanics